Aesthetic experience in technology education – the role of aesthetics for learning in lower secondary school robotic programming - Andrée, Maria; Anderhag, Per; Björnhammer, Sebastian; Salomonsson, Niklas (Frontiers in Education, 2024)
Introduction Within the technology education research field, aesthetics has primarily been treated as either related to artifacts, design processes and innovation, or as related to students’ enjoyment, appreciation, and participation in technology and technology education. This study focuses on the role of aesthetics in technology learning more specifically the learning of programming. Previous research has pointed to aesthetics as important for the learning of programming, e.g., that programming activities in higher education typically involve experiences of frustration. While previous research is primarily based on student reports, there is a need for further exploration of processes of learning to program. The aim of this study is to explore the role of aesthetics for student learning to program in and what these processes may mean in relation to a disciplinary aesthetics of the technology subject. Methods The study was part of a design-based study with the overall purpose to develop the teaching of programming in lower secondary school. Data was collected from a programming task designed and implemented in school-year 9 (the students were aged 15–16) in Technology in two lower secondary classes. In total, three teachers participated in the implementation. The students pair-programmed Lego robots that should perform specific movements, such as following a curved line. Each group recorded their coding process along with audio, resulting in videos that documented the gradual evolution of their programs. These videos, capturing the real-time programming and associated student and teacher conversations, serve as the data for this study. In order to analyze the role of aesthetics in classroom conversations a Practical Epistemology Analysis was applied. Results The results show that aesthetic judgments were important for orienting learning toward (1) the movement of the robot and (2) the ways to be in the programming activity. During the programming activity, the students expressed feelings of frustration but also joy and humor. Discussion The findings concur with previous research and contribute to further understanding the role of negative and positive aesthetic experiences in the teaching and learning of programming. The importance of the objects of aesthetic experience found in this study are discussed as part of a disciplinary aesthetic of programming.